The income approach to property valuation - Baum, Andrew E.; Mackmin, David; Nunnington, Nick. (Amsterdam : Elsevier/EG Books, 2011)
This text covers the latest valuation techniques, including the impo rtant area of investment appraisals. It will help readers understand th e complex world of property valuation.
Includes bibliographical references (p. [331]-332) and index.
Keywords: Real property -- Valuation -- Great Britain; Real estate investment -- Great Britain